DNA twist, flexibility and transcription of the osmoregulated proU promoter of Salmonella typhimurium. - Jordi, B J (1995)
Transcription from many bacterial promoters is sensitive to the level of DNA supercoiling. We have investigated the mechanism by which environmentally induced changes in DNA supercoiling might regulate transcription. For the proU promoter of Salmonella typhimurium, osmotically induced changes in DNA topology appear to play a primary regulatory role. Changes in DNA supercoiling (linking number; delta Lk) are partitioned into changes in the winding of the strands of the double helix about themselves (twist; delta Tw) and/or elastic deformations or flexibility of the DNA helix (writhe; delta Wr). Mutations of the proU promoter were isolated in vivo, or generated in vitro, which altered the spacing between the -10 and -35 motifs. Studies on these mutant promoters, both in vivo and in vitro, exclude models in which changes in DNA twist play a regulatory role. Instead, our data suggest that increased DNA flexibility, reflecting the osmotically induced increase in negative supercoiling of DNA, is required for promoter activation.